141k views
5 votes
Y=3x-2
y=2x-5
how to solve this math problem​

1 Answer

6 votes

Answer:

x = -3

y = -11

Explanation:

You want to substitute one of the y's

3x - 2 = 2x - 5

+2 +2

3x = 2x - 3

-2x -2x

x = -3

now that you have x, you need to substitute the x to get y

y = 3x - 2

y = 3(-3) - 2

y = -9 - 2

y = -11

or

y=2x-5

y = 2(-3) - 5

y = -6 - 5

y = -11

*they will both be the same no matter which equation you use

Hope this helped!

User Xgdgsc
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.